The Occasional Muse: Textual Genesis and Literary Innovation in Komnenian Byzantium (Interfaces: A Journal of Medieval European Literatures, 2024)
This paper explores the literary production of the twelfth century from the perspective of innovation. Focusing on occasion rather than occasionality, and understanding it as 'event' or kairos, it reminds us that the assumed constant of occasion and patronage sometimes needs to be teased apart. The Byzantine twelfth-century production is divided into four groups: 1) Commissioned occasional performative texts; 2) Commissioned non-occasional non-performative texts; 3) Not commissioned occasional (or non-occasional) performative (or non-performative), job-related texts; and 4) Not commissioned non-occasional highly experimental texts. Even if these categories admittedly remain somewhat crude and overlapping, the analysis shows, in particular, how the fourth group contains a large number of works that do not fit into a model of dominant patronage and pervasive occasionality. These are texts marked by hybridity and experimentation, perhaps aimed at achieving commissions through performance in the literary circles of Constantinople, the so-called theatra, but possibly written by authors for themselves or friends, relying on a 'poetics of hybridity.'
Keywords: innovation; hybridity; occasional literature; poetics; performance